A more comprehensive measure of vaccine hesitancy: Creation of the Multidimensional Vaccine Hesitancy Scale (MVHS). (September 2022) - Howard, Matt C.
This article aimed to develop the Multidimensional Vaccine Hesitancy Scale (MVHS). In Study 1 ( n = 336), we identified 13 possible vaccine hesitancy dimensions and developed an item list. In Study 2 ( n = 444), we performed an exploratory factor analysis that supported an eight-dimension structure and reduced our measure to 32 items. We supported its validity by establishing relations with associated variables, even while controlling for measures of the same and similar constructs. In Study 3 ( n = 575), we confirmed its factor structure and replicated its validity results. Support was provided for the psychometric properties and validity of the MVHS.